ANALISIS KEUNTUNGAN INDUSTRI RUMAH TANGGA TEMPE â€œBMLâ€ DI KELURAHAN KOLONGAN SATU KECAMATAN TOMOHON TENGAH KOTA TOMOHON - Febiola Vanessa Ide; Audrey Julia Maria Maweikere; Jean Fanny Junita Timban (Sam Ratulangi University, 2021)
The purpose of this study was to analyze the PROFIT of Tempe â€œBMLâ€ home industry in Kolongan Satu Village, Tomohon Tengah District, Tomohon City. This research was conducted for three months starting from May to July 2021. The data used in this study were primary data and secondary data. Primary data were obtained from direct interviews with the owners of the â€œBMLâ€ tempe home industry. While secondary data was obtained from the Tomohon Tengah District office, available books, and the internet such as a google search to access articles from various scientific journals and theses from other universities related to the research title, especially regarding profit analysis. The results of this study indicate that the home industry of tempe is profitable. Profit in July 2021 is Rp. 6,072,060 with an R/C ratio of 2.91.